In-situ Thermoelectrochemistry: Working with Heated Electrodes - Gründler, Peter (Springer, 2015)
This book represents the first rigorous treatment of thermoelectrochemistry, providing an overview that will stimulate electrochemists to develop and apply modern thermoelectrochemical methods. While classical static approaches are also covered, the emphasis lies on methods that make it possible to independently vary temperature such as in-situ heating of electrodes by means of electric current, microwaves or lasers. For the first time, “hot-wire electrochemistry” is examined in detail. The theoretical background presented addresses all aspects of temperature impacts in the context of electrochemistry.